Policy Analysis for Equitable Distribution of Islamic Senior High Schools in Underdeveloped Regions - Sarini (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The unequal distribution of Madrasah Aliyah (Islamic Senior High School) between urban and underdeveloped areas in Indonesia is a major obstacle to achieving equitable access to secondary education. This policy paper aims to analyze the urgency of equalizing educational units through the integration of geospatial information systems and affirmative action policies. Currently, madrasah development is still dominated by an urban bias paradigm that prioritizes densely populated areas for fiscal efficiency, thus creating a blank spot phenomenon or blind access areas in remote areas. As a result, there is a stagnation in the Gross Enrollment Rate (APK) and an increase in the dropout rate among Madrasah Tsanawiyah graduates in remote areas due to geographic barriers and extreme travel distances. The policy methodology used in this study is a descriptive-qualitative approach with problem priority analysis using the Urgency, Seriousness, and Growth (USG) method. Primary and secondary data are processed through School Mapping techniques and spatial analysis to identify the level of accessibility of educational services. Next, an analysis of alternative policies is conducted to weigh the effectiveness of community-based development models, urban moratorium policies, and the development of Geographic Information System (GIS)-based roadmaps. Risk mitigation was also developed to map technical, fiscal, and operational barriers to policy implementation on the ground. The analysis recommends the government immediately adopt a GIS-based Madrasah Equity Roadmap as a basis for objective decision-making. This strategy must be accompanied by a moratorium on madrasah development in saturated urban areas to redistribute the budget affirmatively to underdeveloped areas.